A Guide for Diagnostic Evaluations - Peeling, R. W.; Smith, P. G.; Bossuyt, P. M. (2012)
Accurate diagnostic tests have a key role in patient management and the control of most infectious diseases. Unfortunately, in many developing countries, clinical care is often critically compromised by the lack of regulatory controls on the quality of these tests. The information available on the performance of a diagnostic test can be biased or flawed because of failings in the design of the studies which assessed the performance characteristics of the test. As a result, diagnostic tests are sold and used in much of the developing world without evidence of effectiveness. Misdiagnosis leading to failure to treat a serious infection or wasting expensive treatment on people who are not infected remains a serious obstacle to health.